Impact of Saccharomyces cerevisiae DSM 34246 (Canobios-BL) var. boulardii Supplementation on Nutritional Status and Fecal Parameters in Healthy Breeding Adult Cats - Nicolò Lonigro; Elisa Martello; Natascia Bruni; Mauro Bigliati; Annalisa Costale; Ilaria Lippi; Giorgia Meineri; Francesca Perondi (Veterinary Sciences)
Recent studies in veterinary science highlight the close relationship between pet health and gastrointestinal health [...]